One & only - Goo, Maurene (G.P. Putnam's Sons, 2026)
"Cassia Park believes in soul mates. Fated love stories. It's her family business, after all...for centuries, from Korea to Los Angeles. Park women have peered into clients' past lives to find their one true love, their fated. This magical secret is why One & Only Matchmaking has a 100% guarantee...for everyone but Cassia. For ten years, Cassia has been searching for her fated, a man named Daniel Nam. But he's still nowhere to be found. And so, on the eve of her 40th birthday, Cass decides to do something for herself. She impulsively has a fling with Ellis. He's 28, indecently handsome, and not destined to be the love of her life. But she's surprised by their connection and their fling feels like something more -- up to the moment he introduces her to his boss -- Daniel Nam! As the battles between fate and chance, head and heart, a family secret is revealed that will make her question everything she's ever known. Cassia will have to decide if she'll follow her fate...or make her own." -- Publisher description.